Research on railway vehicle performance of passing through turnouts forward at 160 km/h - LYU Xiaoyong; WANG Yong; ZHANG Xiaoping; ZHANG Boning; ZHANG Shengjian (机车电传动)
This paper first introduced the principle and process of modeling turnouts by the multi-body dynamics software Simpack, and then expounded the process to solve the wheel-rail contact geometric relationship in the turnout area using the trajectory method programmed by MATLAB and based on the measured data of No. 12 speeding-up turnout profile and JM3 tread, and accordingly revealed the distribution of wheel-rail contact points in different turnout areas as the study results. A vehicle-turnout dynamic interaction model was first established by Simpack in the current study according to the characteristics of 160 km/h railway vehicles, to simulate the dynamic response of the vehicle passing through turnouts at 160 km/h directly and inversely before and after the tread wear, and to discuss the impact of the stiffness and damping of the vehicle's lateral damper and anti-hunting damper on the hunting motion in the turnout area. The results show that the continuous changes of wheel-rail contact geometry in the turnout area is an important factor affecting the dynamic performance of the turnout area. To be specific, when the vehicle passes through turnouts with discontinuous wheel-rail contact points, the wheel-rail coupling is vulnerable to impact, which is mainly represented by the vertical impact and vibration at the frog, and any sudden change of the contact points also causes lateral vibration. The vehicle with over-worn treads suffers from the hunting motion when passing through turnouts at a high speed, which can be suppressed by adjusting the parameters of the anti-hunting damper and lateral damper, as a move to improve the dynamic performance of the vehicle passing through turnouts.